2011
DOI: 10.2174/1876531901103010020
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement Effect at Local Reflectance and Emission Back to Apertureless SNOM Tips in the Shear-Force Gap

Abstract: Physical basics, technique, equipment, proper experimental conditions, and performance of apertureless reflection back-to-the-fiber SNOM (Rayleigh, Raman, fluorescence) under shear-force control are reported. This technique achieves optical resolutions of < 10 nm on flat surfaces and < 20 nm in the presence of topographies with very sharp tips (< 10 -20 nm end radius). It works due to the large enhancement of the reflection to very sharp tapered uncoated tips in the shear-force gap. The dependence of preset vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The scanning probe microscopy is also useful for the study of self-assembled structures producing nanorods, nanosheets, nanocrystals, and so on [7][8][9][10]. It is interesting that the crystallization of self-organized assemblies of mono-protonated TPP (meso-tetraphenyl-porphine) dimers in thin layers, which contain the confined water, has own remarkable features as found earlier by AFM [11].…”
Section: Introductionmentioning
confidence: 82%
“…The scanning probe microscopy is also useful for the study of self-assembled structures producing nanorods, nanosheets, nanocrystals, and so on [7][8][9][10]. It is interesting that the crystallization of self-organized assemblies of mono-protonated TPP (meso-tetraphenyl-porphine) dimers in thin layers, which contain the confined water, has own remarkable features as found earlier by AFM [11].…”
Section: Introductionmentioning
confidence: 82%
“…[8]. Independent support of the three-stage mechanism was provided by grazing incidence diffraction (GID) of reacting crystals [36] and by the chemical contrast of SNOM [7,9,10]. We are now in a situation to proceed with a systematic discussion of intracrystalline and intercrystalline and gas-solid thermal or photochemical molecular (including salts) solid-state reactions of all types on a sound mechanistic basis.…”
Section: Mechanismmentioning
confidence: 99%
“…Further images can be found in the cited original publications. In addition, scanning near-field optical microscopy (SNOM) on rough surfaces was developed to independently secure these facts [8][9][10]. If the crystal packing does not offer a means for migration, there will be no chemical reaction independent of short distances of the centers of a putative reaction and that can be shown by the lack of slip planes, channels, and appropriate voids for accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the optical images of samples on surfaces are altered by humidity and water condensation. Previous studies on the optical signal under variable environmental humidity [2,3] have shown the conditional increase in the optical signal depending on the hydrophobic character of the sample. In fact, the inclusion of water condensation should be considered for any modeling or simulation of the field enhancement effect [3].…”
Section: Introductionmentioning
confidence: 99%